Análisis de la integración en la plataforma moodle con el sistema integrado académico (sai) para mejorar procesos académicos de los docentes de la Universidad Técnica De Babahoyo. - Chiguano Rivera, Andrea Adriana (2023)
, after having enrolled through the enrollment module of the Integrated Academic System (SAI). Through the analysis of the At present, technology has constantly evolved in all areas and has been of help to all citizens, but this has been of great importance for education, not only for students but also for teachers. Higher education has had to adapt to all these changes and innovating all these processes that favor student life. In recent years, virtual learning environments have emerged, offering different ranges of sophisticated options in terms of educational technology. As well as homework and learning environments in educational institutions around the world. Virtual is defined as an interactive educational software, it has integrated communication capabilities, i.e. it communicates with new technologies. There are more than 200 million Moodle users worldwide (as of August 2020), including academic and business users of the most widely used learning platform in the world and in Mexico (more than 70% of higher education institutions according to this study). (moodle, 2022). This analysis of the integration of the two platforms would benefit UTB teachers by being able to count almost immediately with their respective users (students) of the Moodle virtual platformaforementioned platforms, it has been determined that they are not integrated with the same database, thus inconsistency of information regarding the subjects, courses created and user accounts is visualized